Sustainable tourism and renewable energy’s potential: a local development proposal for the La Florida community, Huaral, Peru - Riojas-Díaz, Kiara (2022)
Tourism contributes 10% to global gross domestic product (GDP), yet it generates 5% of all anthropogenic CO2 , while 50 to 60% of carbon emissions are indirectly related to the sector. High levels of poverty afflict rural areas in developing countries, and sustainable tourism based on renewable energy is an ideal approach to generate local development. Our objectives are thus to gauge sustainable tourism’s influence on local development in the community of La Florida, Huaral, Peru and to evaluate the potential of renewable energy (solar and wind power) to propose an eco-efficient business alternative. A non-experimental, quantitative approach was used, in which 265 local residents completed a survey to ascertain their perspectives on the proposal. Moreover, the potential for solar and wind energy was measured to identify sustainable alternatives that residents might incorporate into local ventures. The results demonstrate a relationship between sustainable tourism and local development, as tourism activity enables community members to improve their quality of life and offers them the opportunity to generate new enterprises. Likewise, the assessment of renewable energy potential confirms its feasibility in this area.